Target capture sequencing for phylogenomic and population studies in the Southeast Asian genus Palaquium (Sapotaceae) - Phang, Aireen; Pezzini, Flávia Fonseca; Burslem, David F R P; Khew, Gillian S; Middleton, David J; Ruhsam, Markus; Wilkie, Peter (Botanical journal of the Linnean Society, 2023)
Abstract The first phylogenomic study using a custom target capture bait panel within the Isonandreae tribe in Sapotaceae is presented. The combination of taxon-specific and universal loci from the Angiosperms353 probe set achieved high species resolution within the genus Palaquium and provides the first phylogenomic insights into Malesian representatives of Sapotaceae, where relationships between taxa often remain poorly understood. The results highlight that generic and some species circumscriptions require further investigation and possible revision: Aulandra longifolia is found to be nested in Palaquium, and P. rostratum within P. microphyllum. Population structure analysis produced limited resolution between and within species, but the bait set was able to recover parameters that are potentially useful in population genomic studies.